Navigating in a value-driven practice: a study of a Dutch Recovery College as a learning, social, and organizational space - van Wezel, Marloes M. C.; Muusse, Christien; Boumans, Jenny; Scheerstra, Floris J. A.; Broos, Annelies; Lize, Judith; Leunen, Kelly; Kole, Martijn P. M.; Verspoor, Anthony (Ton); van de Mheen, Dike; Kroon, Hans (Frontiers in Psychiatry, 2025)
IntroductionRecovery Colleges (RCs) facilitate a peer-supported learning environment, co-created bottom-up for and by people with mental vulnerabilities. They explicitly aim to facilitate something different from traditional mental healthcare services, as their ideology is rooted in an emancipatory movement (with focus on peer support, empowerment, and personal recovery). RCs’ ideology comes with key peer support values such as equity, reciprocity, connectedness and empowerment. This study provides an experiential description of an RC practice, scrutinizing how peer support (PS) values are enacted and how partakers experience such value-driven practice.MethodsThis study employs triangulation by combining twin-interviews, participatory observations (with auto-ethnographic elements), and (internal) documentation. All aspects of this study were co-created with experiential researchers who are RC partakers. 26 RC partakers were interviewed by a duo of an academic and an experiential researcher. Additionally, the first author conducted participatory observations over several years.ResultsRC practice is described as a learning, social, and organizational space, each with their own physical and experiential elements. Our analysis showed that enacting PS values ultimately was about making or holding space, which was experienced as carrying both opportunities and challenges for recovery. We zoom in on challenges regarding collaborative learning, taking up and safeguarding space, and organizational growth.DiscussionOur findings highlight how RCs facilitate opportunities for recovery by fostering spaces for collaborative learning, mutual support and co-creation, while also revealing the fragility of these spaces. Experiences in RC practice are highly context- and person dependent. Navigating in such practice therefore requires continuous reflection and dialogue among all involved. To allow for such a culture to emerge and sustain, organizational free space should be safeguarded, minimizing constraints or interference from external parties.